INTEGRASI NILAI-NILAI AL-QUR’AN DALAM PENDEKATAN KONSELING: TINJAUAN KESEHATAN MENTAL REMAJA KORBAN CYBERBULLYING - Nora Afnita; Abdul Kadir; Martin Kustati; Nana Sepriyanti; Joni Indra Wandi (Universitas Negeri Padang, 2024)
Cyberbullying has become a serious threat to the mental health of adolescents in the digital era. Its impacts include depression, anxiety, low self-esteem, and the risk of deviant behavior. A counseling approach based on the values of the Qur'an offers an alternative solution to address these issues through Islamic principles such as compassion (rahmah), wisdom (hikmah), and counsel (mau‘izhah). This study aims to analyze the role of integrating Qur'anic values in counseling to enhance the mental health of adolescents who are victims of cyberbullying. The research employs a descriptive qualitative approach with literature study and phenomenological analysis of relevant Qur'anic verses and the literature on mental health in Islam. The findings indicate that a Qur'an-based counseling approach can help adolescents develop resilience, cope with emotional stress, and build a strong Islamic identity. Therefore, this approach can serve as a practical guide for Islamic counselors in addressing the mental health issues of adolescents.